2004
DOI: 10.2337/diacare.27.6.1343
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Roles of Microvascular and Nerve Function in Foot Ulceration in Type 2 Diabetes

Abstract: OBJECTIVE -To determine the relative roles of different modalities of sensory nerve function (large and small fiber) and the role of microvascular dysfunction in foot ulceration in type 2 diabetic subjects. RESEARCH DESIGN AND METHODS-A total of 20 control subjects and 18 type 2 diabetic subjects with foot ulceration and 20 without were studied. None of the subjects had clinical features of peripheral vascular disease. The Computer-Aided Sensory Evaluator IV (CASE IV) was used to determine vibration detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…The reduction in LDImax in type 2 diabetic subjects confirms our previous observations and those of others (46,47,55). The pathogenesis of this abnormality is not fully understood, but we have previously demonstrated in type 1 diabetic subjects an inverse relationship with capillary basement membrane thickness and have suggested that this may limit microvascular distensibility (56).…”
Section: Studies In Type 2 Diabetessupporting
confidence: 90%
“…The reduction in LDImax in type 2 diabetic subjects confirms our previous observations and those of others (46,47,55). The pathogenesis of this abnormality is not fully understood, but we have previously demonstrated in type 1 diabetic subjects an inverse relationship with capillary basement membrane thickness and have suggested that this may limit microvascular distensibility (56).…”
Section: Studies In Type 2 Diabetessupporting
confidence: 90%
“…Krishnan et al did not show any difference in microcirculatory function between diabetic patients with and without a history of foot ulcer. 33 Furthermore, there was no relationship between wound healing and microvascular dysfunction in diabetic patients and control individuals.…”
Section: Discussionmentioning
confidence: 97%
“…blood capillary buds appeared and fibroblasts began to proliferate, and the blood capillary which was regarded as nutrition supplier provided material needed for wound healing 48) and fibroblast proliferation was required to repair the skin structural defect; in the final stage, tissue extracellular matrix formation and reconstruction was initiated. 49) Previous study showed that aFGF mainly enhanced fibroblast mitosis to accelerate diabetic wound healing.…”
Section: Discussionmentioning
confidence: 99%